MENINGKATKAN SIKAP GOTONG ROYONG DAN PRESTASI BELAJAR BAHASA INDONESIA MELALUI MODEL TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PEMBELAJARAN PERMAINAN TRADISIONAL - Alfina Dwi Riyanti; Asih Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to increase mutual cooperation and student learning achievement through the TGT model assisted by traditional game media in Indonesian language learning among 4th graders. Conducted in three cyclesin which each consisted of two meetings, the research includes 23 students. Data were collected using observation sheets, evaluation sheets, questionnaires, and documentation. The results of this study showed a gradual increase in the attitude of mutual cooperation and student learning achievement. In the first cycle, the attitude of mutual cooperation reached a level of completeness of 55.08% (good enough), and in the second cycle with a completeness of 68.04% (good), and in the third cycle with a completeness of 79.69% (good). Similarly, learning achievement resulted in an average score of 64.9 with a completeness rate of 47.82% (poor), and in the second cycle the average score was 75.8 with a completeness rate of 67.38% (good), and in the third cycle the average score was 80.8 with a completeness rate of 82.60% (very good). The study shows that TGT model assisted by traditional games has a positive impact on students' mutual cooperation attitude.